A Study of Mobile Sensing Using Smartphones - Ming Liu (International Journal of Distributed Sensor Networks)
Traditional mobile sensing-based applications use extra equipments which are unrealistic for most users. Smartphones develop in a rapid speed in recent years, and they are becoming indispensable carry-on of daily life. The sensors embedded in them provide various possibilities for mobile applications, and these applications are helping and changing the way of our living. In this paper, we analyze and discuss existing mobile applications; after that, future directions are pointed out.